Chronic inflammation and angiogenic signaling axis impairs differentiation of dental-pulp stem cells. - Michael Boyle; Crystal Chun; Chelsee Strojny; Raghuvaran Narayanan; Amelia Bartholomew; Premanand Sundivakkam; Satish Alapati (PLoS ONE)
Dental-pulp tissue is often exposed to inflammatory injury. Sequested growth factors or angiogenic signaling proteins that are released following inflammatory injury play a pivotal role in the formation of reparative dentin. While limited or moderate angiogenesis may be helpful for dental pulp maintenance, the induction of significant level of angiogenesis is probably highly detrimental. Hitherto, several studies have addressed the effects of proinflammatory stimuli on the survival and differentiation of dental-pulp stem cells (DPSC), in vitro. However, the mechanisms communal to the inflammatory and angiogenic signaling involved in DPSC survival and differentiation remain unknown. Our studies observed that short-term exposure to TNF-α (6 and 12 hours [hrs]) induced apoptosis with an upregulation of VEGF expression and NF-κB signaling. However, long-term (chronic) exposure (14 days) to TNF-α resulted in an increased proliferation with a concomitant shortening of the telomere length. Interestingly, DPSC pretreated with Nemo binding domain (NBD) peptide (a cell permeable NF-κB inhibitor) significantly ameliorated TNF-α- and/or VEGF-induced proliferation and the shortening of telomere length. NBD peptide pretreatment significantly improved TNF-α-induced downregulation of proteins essential for differentiation, such as bone morphogenic proteins (BMP)-1 & 2, BMP receptor isoforms-1&2, trasnforming growth factor (TGF), osteoactivin and osteocalcin. Additionally, inhibition of NF-κB signaling markedly increased the mineralization potential, a process abrogated by chronic exposure to TNF-α. Thus, our studies demonstrated that chronic inflammation mediates telomere shortening via NF-κB signaling in human DPSC. Resultant chromosomal instability leads to an emergence of increased proliferation of DPSC, while negatively regulating the differentiation of DPSC, in vitro.